Physico-chemical changes in dabai (Canarium odontophyllum Miq.) fruit during modified atmosphere storage - Ding, Phebe; J., Diana (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Dabai or Canarium odontophyllum Miq., from the family Burseraceae, is an important indigenous fruit to Borneo Island. However, it is a highly perishable fruit with short shelf life. Postharvest technology such as modified atmosphere packaging (MAP) can be used to maintain highly perishable fresh fruit quality and increase its shelf life. There is not much work has been carried out to study effect of MAP on dabai fruit. Therefore, this study was conducted to determine the effect of four different types packaging methods on the postharvest quality of dabai fruits. Total of 240 fruit were used for each replication and the experiment was repeated thrice. Fruit were divided equally into four groups with each group packed in low-density polyethylene plastic bag, low-density polyethylene plastic bags lined with tissue paper, low-density polyethylene plastic bag with vacuumed and control (unwrapped). The fruit were then stored in a cold room of 10°C for 8 days. The fruits were analyzed for peel and flesh colour (L* , C* and hue angle), CO2 and C2H4 production, weight loss, firmness, soluble solids concentration (SSC), titratable acidity (TA) and pH at every two days interval. Data were analyzed using analysis of variance and means was separated using Duncan's multiple range tests. The use of MAP retained peel colour (L* , C* and hue angle values), flesh colour (L* values), SSC and TA of dabai fruit. The CO2 production in MAP fruit was significant lower than control. Although vacuum packed showed lowest weight loss, flesh discolouration, soggy texture and foul sour odour developed during 8 days of storage. Neither packing dabai fruit in low-density polyethylene plastic bag nor bag lined with tissue paper retained better fruit quality. Thus, it is recommended packing dabai fruit in low-density polyethylene plastic bag is sufficient to retain fruit quality during 8 days of storage at 10°C.